2018
DOI: 10.1101/303115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reproducible functional connectivity alterations are associated with autism spectrum disorder

Abstract: Despite the high clinical burden little is known about pathophysiology underlying autism spectrum disorder (ASD). Recent resting state functional magnetic resonance imaging (rs-fMRI) studies have found atypical synchronization of brain activity in ASD. However, no consensus has been reached on the nature and clinical relevance of these alterations. Here we address these questions in the most comprehensive, large-scale effort to date comprising evaluation of four large ASD cohorts. We followed a strict explorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…These results are also consistent with previous studies finding altered Glx levels in ASD [80][81][82][83][84][85][86][87][88][89] . We also identified a strong positive association between SM1 and Thal Glx in the ASD group that was otherwise absent in the TDC group, supporting the well-replicated and robust findings of hyperconnectivity between thalamic and sensory cortical regions in ASD [90][91][92][93][94] .…”
Section: Discussionsupporting
confidence: 71%
“…These results are also consistent with previous studies finding altered Glx levels in ASD [80][81][82][83][84][85][86][87][88][89] . We also identified a strong positive association between SM1 and Thal Glx in the ASD group that was otherwise absent in the TDC group, supporting the well-replicated and robust findings of hyperconnectivity between thalamic and sensory cortical regions in ASD [90][91][92][93][94] .…”
Section: Discussionsupporting
confidence: 71%
“…Similarly, the addition of multidimensional phenotyping data to include behavioral readouts may help to assess the translational significance of the mapped brain (dys)connectivity signatures, as it might reveal their relationship with core deficits that characterize ASD. It should however be noted that the relationship between connectivity findings and ASD-behavioural traits remains contentious: while prior mouse work has revealed a possible link between network-specific dysconnectivity and specific ASD-related behavioural traits, recent clinical meta-analyses suggest that rsfMRI connectivity is a poor predictor of ASD symptomatology 13 . Our observation of diverging connectivity across models characterized by partly-concordant behavioural deficits is consistent with the notion that ASD-related behavioural dysfunction cannot be monotonically represented in connectional terms.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, a growing number of studies in idiopathic 7 , 8 as well as syndromic forms of ASD 9 12 has suggested that aberrant connectivity in ASD could be detected by resting-state fMRI (rsfMRI). However, whilst a recent aggregate analysis has revealed a putatively reproducible mosaic pattern of atypical connectivity in ASD 13 , the heterogeneity in rsfMRI connectivity findings across ASD cohorts is considerable, and unlikely to reflect technical or procedural discrepancies in imaging acquisitions and analysis 2 , 12 , 14 . Hence, one outstanding question in the field is whether ASD can be associated with a univocal, diagnosis-specific signature of dysfunctional brain connectivity that is common to the whole spectrum, or whether clinical heterogeneity is the sum of distinct and separable signatures of network dysfunction.…”
Section: Introductionmentioning
confidence: 98%
“…At the macroscopic level, several studies have highlighted the presence of aberrant functional connectivity in ASD as measured with resting state fMRI (rsfMRI) (Supekar et al, 2013;Uddin et al, 2013;Hong et al, 2020), electroencephalography (Murias et al, 2007) or nearinfrared spectroscopy (Kikuchi et al, 2013). These observations suggest that specific symptoms and clinical manifestations of ASD could at least partly reflect interareal brain synchronization (Di Martino et al, 2009;Holiga et al, 2018). Although the exact relationship between microscopic, mesoscopic and large-scale network activity remains poorly understood, the linear integrative function served by dendritic spines (Cash and Yuste, 1999) may be critical to the establishment of large-scale interareal coupling.…”
Section: Introductionmentioning
confidence: 99%